Ameloblastoma of the Posterior Mandible: Radical Resection and Reconstruction Using Osteofaciocutaneous Free Fibular Flap - Kadir Naneci; Poyzan Bozkurt; Mitat Selçuk Bozhöyük; Süha Beton; Burak Kaya; Mehmet Eray Kolsuz (Ankara University, 2022)
This study reports a case of an ameloblastoma in the posterior region of the right mandible in a 38-year-old female patient. The diagnosis was made after needle aspiration biopsy and resection treatment was planned. The resected mandible was constructed via osteofaciocutaneous free fibular flap. Today, this treatment option is considered the gold standard and in the present case, treatment results were favorable.